The Influence of Corporate Social Responsibility Disclosure on Firm Value (Empirical Study on Energy Sector Companies Listed on the IDX for the Period 2021-2023) - Elizabeth Remora, Sonia; Hasnawati, Hasnawati (DINASTI RESEARCH, 2025)
This study aims to examine the influence of Corporate Social Responsibility disclosure, economic disclosure, environmental disclosure, and social disclosure on company value. The population in this study is energy sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sample in this study is 119 companies that were selected using the purposive sampling technique, which is the determination of samples using certain criteria. This study uses a multiple linear regression analysis method and uses the SPSS (Software Product and Service Solution) version 24 program in data processing. The results show that CSR disclosure and economic disclosure have a positive influence on company value, while environmental disclosure and social disclosure have no effect on company value.